2018
DOI: 10.3390/resources7040075
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Influence of Rhamnolipid Bio-Surfactant on the Carbonate Rock/Water/Oil Interaction at Elevated Temperature

Abstract: Tertiary recovery is directly dependent on the alteration in wettability and interfacial tension (IFT), hence releasing the trapped oil from rock pore spaces. Bio-surfactant water flooding to mobilise residual oil in reservoirs is a new and developing prospect that can be used more often in future due to its environmentally friendly nature and economic advantages. In this work, the impact of rhamnolipids as water soluble bio-surfactant solutions on the interfacial activities of saline water and the wettability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This variation is attributed to several factors, including the composition and structure of the mineral phase in the column or core, temperature, medium acidity, salinity, and the chemical structure of the surfactant. It is well known that the steric characteristics of molecules play a vital role in the formation of micelles [6,[55][56][57][58][59].…”
Section: Meor Simulationmentioning
confidence: 99%
“…This variation is attributed to several factors, including the composition and structure of the mineral phase in the column or core, temperature, medium acidity, salinity, and the chemical structure of the surfactant. It is well known that the steric characteristics of molecules play a vital role in the formation of micelles [6,[55][56][57][58][59].…”
Section: Meor Simulationmentioning
confidence: 99%
“…Biosurfactant flooding is another important bio-EOR technique. Biosurfactants can reduce the interfacial tension (IFT) between the oil and water phases and also change the wettability state of the matrix from oil-wet to water-wet; hence, water can move easily through the rock pores due to reductions in capillary forces. Recently, Cheng et al have studied the effect of surfactant flooding in a fractured core, and their results indicated that the movement of the surfactant through the matrix depends strongly on diffusion so that increasing the injection rate led to increased oil recovery. Spinler et al carried out an experiment using a surfactant in chalk cores to enhance forced and spontaneous imbibition.…”
Section: Introductionmentioning
confidence: 99%